The pricing of exchange risk in emerging stock markets - Carrieri, Francesca; Majerbi, Basma (Journal of International Business Studies, 2006)
In this paper, we provide new evidence about the unconditional pricing of exchange risk in the stock market, based on emerging market data. We conduct empirical tests using cross-sectional data at the market, portfolio and firm level from nine emerging markets (EMs) to determine whether exchange risk is priced under alternative model specifications and exchange rate measures. Our results support the hypothesis of a significant unconditional exchange risk premium in emerging stock markets, differently from most unconditional tests for major developed markets. However, there is indication that at the aggregate market level the significance of the exchange risk factor is subsumed by local market risk. With firm-level data, although the importance of local market is confirmed for most countries, some measure of exchange rate risk remains significant for most countries. This suggests that a careful model specification is necessary for EMs when testing for the pricing of exchange risk in order to avoid a potential spurious significance of such factor because of a missing local risk or vice versa.